A Meshless Regularization Method for a Two-Dimensional Two-Phase Linear Inverse Stefan Problem (Advances in Applied Mathematics and Mechanics, 2021)
In this paper, a meshless regularization method of fundamental solutions is proposed fora two-dimensional, two-phase linear inverse Stefan problem. The numerical implementationand analysis are challenging since one needs to handle composite materials in higher dimensions.Furthermore, the inverse Stefan problem is ill-posed since small errors in the input datacause large errors in the desired output solution. Therefore, regularization is necessaryin order to obtain a stable solution. Numerical results for several benchmark test examplesare presented and discussed.